TEACHING USUL AL-FIQH: A MULTICULTURAL EDUCATION MODEL - Rusli Rusli (AL-TAHRIR, 2014)
This paper deals with the teaching of us}u>l al-fiqh (methodology of Islamic law) using a multicultural model. Multiculutral education means an instilling of the values that lead to peace and harmony, which comprise sixteen values, such as equality, mercy, empathy, justice, nationalism, cooperation, tolerance, good opinion, solidarity, mutual trust, self-convidence, responsibility, honesty, sincerity, trustworthy, and deliberation. These values are humanist in nature, and can be found clearly in the primary sources of Islam, such as the Qur’a>n and the Sunna of the Prophet. In the teaching of us}u>l al-fiqh, which is based on a multicultural education, these values should be incorporated into learning. In the process of incorporating these values, the paradigm that is isued is humanist-progressive, which emphasizes the principle and approach of respect for differences and doing more cooperative activities than competitive. In the principle of respect for differences, education is illustrated as mirror, window and conversation, while in the second principle, students are the subject in learning process. The method of teaching that is employed in class includes dialog, cooperation, problem solving, affirmation and democratic boundaries setting.